Beyond Nonalcoholic Fatty Liver Disease: The Expansive Realm of Metabolic Dysfunction-associated Steatotic Liver Disease - Samir Samadarshi; Dharmendra Kumar; Manish Manrai; Saurabh Dawra; Sharad Srivastava; Alok Chandra (Journal of Marine Medical Society)
Background: The Delphi consensus statement has accepted the new fatty liver disease nomenclature. Steatotic liver disease (SLD) is an overarching term that encompasses various etiologies of steatosis. The name chosen to replace nonalcoholic fatty liver disease was metabolic dysfunction-associated SLD (MASLD). Patients having SLD along with underlying cardiometabolic risk factor(s) are labelled as MASLD. We carried out a cross-sectional study of patients with fatty liver visiting the gastroenterology department of a tertiary care hospital to determine the association of cardiometabolic risk factors with significant fibrosis. Materials and Methods: In this cross-sectional study, adults with evidence of fatty liver on abdominal ultrasonography with no history of heavy alcohol use were enrolled. Participants with evidence of chronic liver diseases (including chronic hepatitis, autoimmune hepatitis, and drug-induced hepatitis), people living with HIV/AIDS, and those with disseminated or advanced malignancy were excluded. Anthropometric assessment and hematological and biochemical tests were done, and all participants underwent transient elastography of the liver using FibroScan™. Results: All 135 patients were classified as MASLD as per the new nomenclature accepted by the Delphi consensus. Body mass index (BMI), waist circumference (WC), serum triglycerides (TG), and high-density lipoprotein (HDL) cholesterol were found to have a significant association with liver stiffness measurement (LSM) (adjusted r2 0.23, P < 0.001). 32.5% of participants (n = 44) were found to have significant fibrosis on transient elastography. LSM was significantly higher in patients with metabolic syndrome. Conclusion: Metabolic syndrome is an important risk factor for significant fibrosis. Among various cardiometabolic risk factors, BMI, WC, and serum TG are associated with higher LSM. HDL levels correlate negatively with LSM. The new nomenclature focuses on these cardiometabolic risk factors and has broader applicability.